LA VILLA RENACENTISTA (II) - Vera Botí, Alfredo; Sánchez-Rojas Fenoll, María del Carmen (Imafronte, 1993)
After analyzing the cultural causes which influenced the return of the villas in Italy (see the first part of this paper, in Irnafronte. no 2, 1986), we present now a systematic summary of the main villas built there during the Renaissance, and shou their essential features. Sometimes they tend to present invariant signs coming from local influences, as it happens in Venetian and Genoese villas. Other times, their compositional forms derive from the cultural contributions mude by the authors, who moved from one court to another, or frnm Architecture treutises.